PENGGUNAAN TANGKAI PEGANGAN ROLLER CAT YANG DIMODIFIKASI MENINGKATKAN KINERJA PENGECAT PLAFON RUKAN DI DENPASAR - Haryawan, I Gusti Agung; Sutjana, I Dewa Putu; Sutajaya, I Made (Jurnal Ergonomi Indonesia (The Indonesian Journal of Ergonomic); Vol 2 No 2 (2016): Volume 2 No 2 Desember 2016DO - 10.24843/JEI.2016.v02.i02.p01)
Buildings development is very glowing recently.  This also has effect on manpower who works at this sector.  Manpower is demanded to have skill according to his field.  Worker at finishing field or especially for ceiling painter needs skill and technique that he should master.  While working the worker always assists by tools and paint materials.  Tools that are used by the ceiling painter have not been refered to antropometry aspect, so it can cause inconvenient in performing the job.  Working with toold that are not accorded to ergonomic principle and working posture that is not physiological can cause fatigue, muscle disturbance, musculoskeletal and increasing working load.  That is why it needs to modify painting roller holder stick.  In that case the worker can work in comfort, safe, healthy, efficient and productive so it can increase productivity. This research was perfomed at office house at Denpasar City.  Type of this research is experimental research by using treatment by subject design by involving 16 samples.  Interval between before treatment and after treatment is given washing out for two days.  Data measured are the working load measured by the increasing of subjective complaint recorded by Nordic Body Map questionnaire, pulses, fatigue and working productivity.  Data of subjective complaint was analyzed by non-parametric statistic test using the Wilcoxon test with significance rate of ? = 0.05, data of pulses as indicator of working load,  working productivity was priorly data normality tested by Shapiro-Wilk Test with significance rate of ? = 0.05.  Data that normal distributed is continued with parametric statistic test using the t-paired test at significance rate of ? = 0.05. Research result shows that there is significant different (p<0.05) to working load variable, musculoskeletal complaint, fatigue and productivity.  At before treatment the average of pulses of ceiling painter is 118.95 + 2.30 dpm, average of musculoskeletal complaint is 78.50 + 5.84, average of fatigue is 74.22 + 388 and average of productivity is 0,070 + 0,017.  Whereas, at after treatment the average of pulses of ceiling painter is 111.89 + 6.58 dpm, average of musculoskeletal complaint is 61.61 + 1.71, average of fatigue is 64.50 + 2.88 and average of productivity is 0,086 + 0,070. Modification of painting roller holder stick turned out to decrease working load for 10,77%, musculoskeletal complaint for 21,51%, fatigue for 13,09%, and productivity is increasing for 22,85%. From discussion above it can be concluded that the modification of painting roller holder stick can decrease working load, musculoskeletal complaint, fatigue, and increase productivity.  In that case, it can be expected that the ceiling painter workers use this painting roller holder stick in order to minimize any complaint raises due to working process
Keywords: Painting Roller Holder Stick, Modification, Performance, Ceiling Painter